1999
DOI: 10.1021/jf980999y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Coumarins from Lemon Fruit (Citrus limon) as Inhibitors of in Vitro Tumor Promotion and Superoxide and Nitric Oxide Generation

Abstract: Three coumarins were isolated as siginificant inhibitors of tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced Epstein-Barr virus (EBV) activation in Raji cells from the peel of lemon fruit. They were identified as 8-geranyloxypsolaren (LE-1), 5-geranyloxypsolaren (bergamottin, LE-2), and 5-geranyloxy-7-methoxycoumarin (LE-3), respectively, by spectroscopic analysis. Three isolates had no potential O(2)-scavenging and markedly suppressed TPA-induced superoxide (O(2)(-)) generation in differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…The eriocitrin (eriodictyol 7-rutinoside) from lemon fruit was isolated and its antioxidant capacity was evaluated (Miyake et al 1997). The coumarins from lemon fruit was identified and the inhibition for tumor promotion and superoxide and nitric oxide generation was characterized (Miyake et al 1999). New limonoid glycosides was isolated and their Electronic supplementary material The online version of this article (doi:10.1007/s13197-017-2544-5) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…The eriocitrin (eriodictyol 7-rutinoside) from lemon fruit was isolated and its antioxidant capacity was evaluated (Miyake et al 1997). The coumarins from lemon fruit was identified and the inhibition for tumor promotion and superoxide and nitric oxide generation was characterized (Miyake et al 1999). New limonoid glycosides was isolated and their Electronic supplementary material The online version of this article (doi:10.1007/s13197-017-2544-5) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…They also have anti-inflammatory activity and anti-carcinogenic properties (Miyake et al 1999). On the other hand, the activity of these compounds as food lipid antioxidants is well known (Rice-Evans et al 1997), and this fact promoted studies of extracts from different plants containing them.…”
mentioning
confidence: 99%
“…No cytotoxicity was apparent when the concentration of a coumarin derivative was less than 1:0 Â 10 À4 M. Coumarins inhibited IgE-mediated histamine release from RBL-2H3 cells as well as that of -hexosaminidase release (data not shown). Coumarin derivatives occur in various spice plants, and have been reported to have antitumoral, 15) fungicidal 16) and anti-inflammatory 17) activities. Although Ryu et al 18) have reported that cnidicin, a coumarin derivative, inhibited mast cell degranulation, degranulation inhibiting activity of 7-methoxycoumarin has not previously been reported.…”
Section: Resultsmentioning
confidence: 99%